2014
DOI: 10.1186/s12963-014-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

Global infant mortality trends and attributable determinants – an ecological study using data from 192 countries for the period 1990–2011

Abstract: Background: Infant mortality rate (IMR) is regarded as an important indicator of population health. IMR rates vary substantially with the highest found in sub-Saharan Africa (SSA) compared to the lowest in Europe. Identifying spatial disparities in IMR and quantifying attributable risk factors is essential for policymakers when tailoring time-appropriate interventions at a global, regional, and country level.Methods: Data for 192 countries were extracted from the World Bank Development Indicator database for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 30 publications
2
53
1
1
Order By: Relevance
“…To quantify the contribution (attributability) of each of the different factors to stunting, we used a Shapley regression-based decomposition approach for distributional analysis (Shorrocks, 2013). This approach has been increasingly applied in public health research in recent times due to advantages over the more classical attributable fraction approach and inherent problems with the latter (Rockhill, Newman, & Weinberg, 1998;Sartorius & Sartorius, 2014;Wang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the contribution (attributability) of each of the different factors to stunting, we used a Shapley regression-based decomposition approach for distributional analysis (Shorrocks, 2013). This approach has been increasingly applied in public health research in recent times due to advantages over the more classical attributable fraction approach and inherent problems with the latter (Rockhill, Newman, & Weinberg, 1998;Sartorius & Sartorius, 2014;Wang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported an insignificant association between regional variation and infant mortality [26]. Some other studies have identified that eco-developmental region was significantly associated with infant mortality [4, 7, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduction in infant mortality by two thirds by many countries indicating a progress towards achieving the millennium development goal (MDG)-4 by the year 2015, this has not been evident in sub-Saharan Africa and some Asian countries including Nepal [5, 6]. Hence, disparities and inter-country variations still exist around the world in terms of IMR [7]. Recent trends of childhood deaths in African and Asian countries show that one out of every 12 infants does not survive until adulthood [8].…”
Section: Introductionmentioning
confidence: 99%
“…With high rates of infant mortality in sub-Saharan Africa, investments in infant and child health are subject to tough prioritizations of time and resources within the household, in which maternal preferences for a desired number and gender composition of children may play a part (Jones 2014;Mosley & Chen 1984;Sartorius & Sartorius 2014). Partly for that reason, reducing unwanted childbearing has been regarded as important for improving child health and survival (Günther & Harttgen 2016;Joshi & Schultz 2013;Lloyd & Montgomery 1996).…”
Section: Introductionmentioning
confidence: 99%